2019
DOI: 10.1016/j.aop.2019.167970
|View full text |Cite
|
Sign up to set email alerts
|

Superintegrable systems from block separation of variables and unified derivation of their quadratic algebras

Abstract: We present a new method for constructing D-dimensional minimally superintegrable systems based on block coordinate separation of variables. We give two new families of superintegrable systems with N (N ≤ D) singular terms of the partitioned coordinates and involving arbitrary functions. These Hamiltonians generalize the singular oscillator and Coulomb systems. We derive their exact energy spectra via separation of variables. We also obtain the quadratic algebras satisfied by the integrals of motion of these mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…We observe that the polynomials P 1 and Q 1 do not commute with H 1 at the level of the enveloping algebra, but only as the result of considering the realization (11). Thus the (infinite-dimensional) quadratic algebra determined by ( 16) is only valid for the given realization, and is not an algebraic consequence of the underlying hidden symmetry algebra.…”
Section: Polynomial Algebras Related To the Smorodinsky-winternitz Sy...mentioning
confidence: 92%
See 2 more Smart Citations
“…We observe that the polynomials P 1 and Q 1 do not commute with H 1 at the level of the enveloping algebra, but only as the result of considering the realization (11). Thus the (infinite-dimensional) quadratic algebra determined by ( 16) is only valid for the given realization, and is not an algebraic consequence of the underlying hidden symmetry algebra.…”
Section: Polynomial Algebras Related To the Smorodinsky-winternitz Sy...mentioning
confidence: 92%
“…Other classes of quantum models and superintegrable systems have been studied over the years using different techniques, such as systems characterized by symmetry algebras related to non Abelian polynomial algebras (see e.g. [6][7][8][9][10][11]). The underlying polynomial algebras are constructed via integrals based on explicit differential operator realizations [11], a fact that again poses a more or less severe restriction for their classification and detailed study, as the relations among elements must be understood via a differential operator algebra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that quadratic algebras associated with n-dimensional systems are in general of higher rank [15,16,17,18]. These algebraic structures allow one to obtain useful information on quantum systems and their degenerate spectrum [19].…”
Section: Introductionmentioning
confidence: 99%
“…Separation of variables is a powerful tool in mathematical physics. In [128] and [140], we have applied separation of variables to obtain quadratic algebras. In this chapter, we apply the separation of variables to construct high order integral of motion.…”
Section: Introductionmentioning
confidence: 99%